Розробка компонентів web-порталу вакансiй - Домнiч, Д. В. (ХНУРЕ, 2024)
A class of social and economic systems on the trade market of Ukraine is considered. A social and economic approach for analysis of these systems is recommended. An important type of the processes in such systems is a process of searching for a job by citizens of a country. Development of components of web-system for job portal, which allows simplifying the process of searching and applying for vacancies based on their qualifications, is considered. During the work server and client parts were developed. The system makes it possible to efficiently search, filter out, create, edit, delete and implement job application process.
Keywords: web-портал вакансiй; соціально-економічна система